Comparative Analyses of Villin and HER-2 Genes Expression in Breast Cancer - Mohammadpour, Hadiseh; Hashemi, Mehrdad; shirkoohi, Reza; Saffari, Mojtaba; Emami Razavi, Amir Nader (Archives of Breast Cancer, 2015)
Background: It has been previously demonstrated that HER-2 (human epidermal growth Factor receptor 2) positive breast cancers are associated with an aggressive nature. Villin is an actin bundling protein that plays a key role in actin reorganization and cell remodeling during stress. In this study, we aimed to investigate the correlation of Villin gene expression with HER-2 in breast cancer patients. Methods: Samples of 42 patients with breast cancer, and 3 controls were collected. Expression of Villin and HER-2 genes were monitored with real-time PCR using pre-designed primers. Student T-test was used to compare the means between the groups. Results: The mean age of the patients was 50±4.11years. Expression of the Villin gene was decreased in 28 samples (18 and 10 samples with negative and strongly HER-2 positive, respectively). Villin gene expression was increased in 14 samples (7, 2 and 5 samples with negative, weakly positive, and strongly HER-2 positive, respectively). The expression of Villin was significantly correlated with HER-2 positive status (P = 0.00057) Conclusions: We found that Villin gene expression is associated with HER-2 positivity and may be a predicting factor in aggressive breast cancer.